Structural mechanics of cylindrical fish-cell zero Poisson’s ratio metamaterials - Qin, Qing; Dayyani, Iman; Webb, Phil (Elsevier, 2022)
In this paper, a novel cylindrical metamaterial exhibiting zero Poisson’s ratio in two different directions is introduced. Detailed CAD modelling of a curved Fish-Cells necessary for numerical and experimental analysis are presented. High-fidelity finite element models are developed to assess the homogenisation studies of Poisson’s ratio, Young’s modulus and torsion behaviour, demonstrating the curvature effect and independency of the mechanical behaviour of cylindrical Fish-Cells metamaterial from tessellation numbers. Experimental analysis is performed to validate the zero Poisson’s ratio, deformation and fracture mechanism discussed in numerical simulations. Moreover, buckling and modal behaviours of the cylindrical Fish-Cells metamaterials are studied and compared with equivalent shell models.
Keywords: Lattice Structures; Cylindrical Metamaterial; Zero Poisson's Ratio; Buckling; Modal analysis